Humidified and Heated Cascade Impactor for Aerosol Sizing - Majoral, Caroline; Coates, Allan L.; Le Pape, Alain; Vecellio, Laurent (Frontiers in Bioengineering and Biotechnology, 2020)
This work aimed to develop a humidified and heated cascade impactor and measure particle size at human physiological temperature and humidity (HPTH). Four aerosol devices (jet nebulizer, mesh nebulizer, Metered Dose Inhaler (PMDI), and Dry Powder Inhaler (DPI)) under ambient conditions and at HPTH were tested with an Andersen Cascade Impactor (ACI). An artificial trachea and the ACI was used at ambient temperature or heated to 37°C, and either dry or humidified inside. MMAD was lower at HPTH for the two nebulizers; it was similar at ambient conditions and HPTH for salbutamol PMDI, and the mass of particles smaller than 5µm decreased for terbutaline DPI at HPTH (51.9 µg/puff vs. 82.8 µg/puff). In conclusion, the influence of the HPTH on particle size produced by inhalation products depends on device and drug formulation.